Improving a Lagrangian decomposition for the unconstrained binary quadratic programming problem - Mauri, Geraldo Regis; Lorena, Luiz Antonio Nogueira (Computers & operations research, 2012)
This paper presents a new alternative of Lagrangian decomposition based on column generation technique to solve the unconstrained binary quadratic programming problem. We use a mixed binary linear version of the original quadratic problem with constraints represented by a graph. This graph is partitioned into clusters of vertices forming subproblems whose solutions use the dual variables obtained by a coordinator problem. Computational experiments consider a set of difficult instances and the results are compared against other methods reported recently in the literature.